FACTORS AND METRICS THAT INFLUENCE FRANCHISEE PERFORMANCE: AN APPROACH BASED ON BRAZILIAN FRANCHISES - Aguiar, Helder de Souza (2017)
The article searches to map the manager’s decisions in order to understand what has been the franchisor system for choose regarding to characteristics, and what the metrics has been adopted to measure the performance Though 15 interviews with Brazilian franchise there was confirmation that revenue is the main metric used by national franchises to measure performance, although other indicators are also used in a complementary way. In addition, two other factors were cited by the interviewees as relevant during the performance evaluation: the underinvestment aligned to the presence, and the relationship, influenced by the network time.